Revisitando a influências das tradições místicas na construção do sistema de mundo newtoniano: a dupla face de Jano - Lisboa, Hindemburgo (2015)
This paper presents a study about the relationship between the arcane traditions, alchemy, astrology, Hermeticism, Kabbalah, and the construction of the system of the Newtonian world. The discovery and subsequent publication of Newton‟s scholia drew a man to whom the mythical language and scientific language were converging. Their belief in Prisca Sapientia [pristine wisdom, primeval], led him to an attitude of reverence to the ancients‟ knowledge, hence their immersion in the mystical philosophy whose tenets have exerted a substantial influence in the development of their work. Indeed, we show that to Newton, science and mysticism was a unison reality. His natural philosophy cannot be dissociated from their metaphysical speculations. We also point out the fact that religion and mysticism are instances that do not overlap, and signaled in the text that the historical separation between religion and science was the product of political circumstances rather than philosophical. Comprising mainly literature, this work was constructed from a historical analysis of primary and secondary sources. We based the study of key works by Newton on an exhaustive reading of the leading biographers and commentators of his work, such as Richard S. Westfall, James Gleick, David Berlinski, Richard Brennan, Michael White, Philip Ashley Fanning, Bernard Cohen, John Henry, Betty Jo Teeter Dobbs, Edwin Burtt, among other classic authors. In light of this hermeneutic, we point out the nature, the scope and the implications of mysticism influence in Newtonian work. Isaac Newton‟s life and work emerge as platforms to revisit the ambivalent nature of the modern experimental science origins and foundations. This is the configuration of a new way to make history, producing knowledge under an integral historiographical perspective.